Expert judgment-based fragility assessment of reinforced concrete buildings exposed to fire. (November 2017) - Ioannou, I.; Aspinall, W.; Rush, D.; Bisby, L.; Rossetto, T.
Highlights: The fire fragility of a generic modern, mid-rise, RC office building is assessed. Fragility curves for its slabs and columns are constructed by expert elicitation. The expert elicitation also used to construct a suitable fire damage scale. The significance of spalling in the two RC elements is identified.